2004
DOI: 10.1096/fj.03-1241com
|View full text |Cite
|
Sign up to set email alerts
|

Genetic loci that control the angiogenic response to basic response to basic fibroblast growth factor

Abstract: Angiogenesis is controlled by a balance between stimulatory growth factors and endogenous inhibitors. We propose that the balance of stimulators and inhibitors, as well as the general sensitivity of the endothelium to these factors, varies from individual to individual. Indeed, we have found that individual mouse strains have dramatically different responses to growth factor-induced neovascularization. Quantitative trait loci (QTLs), which influence the extent of angiogenesis induced by vascular endothelial gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 61 publications
(59 reference statements)
2
27
0
Order By: Relevance
“…In support of such a function, a chromosomal region including the ATX gene had been associated with angiogenic responsiveness to FGF2 [88]. However, an essential role of ATX for vascular development was only revealed through the generation of ATX null mice [18,19].…”
Section: Atx: Enzymatic Activity Via the Catalytic Lysopld Active Sitementioning
confidence: 99%
“…In support of such a function, a chromosomal region including the ATX gene had been associated with angiogenic responsiveness to FGF2 [88]. However, an essential role of ATX for vascular development was only revealed through the generation of ATX null mice [18,19].…”
Section: Atx: Enzymatic Activity Via the Catalytic Lysopld Active Sitementioning
confidence: 99%
“…This model has been extensively used to study genetic variations in angiogenic potential (19)(20)(21)(22) and to quantify the effects of pharmacologic agents on angiogenesis (23,24). We found that mice exposed to a single dose of radiation used for bone marrow transplantation exhibited a long-term decrease in capacity to undergo neovascularization and tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, ATX-transfected Ras-transformed NIH 3T3 cells or purified ATX increased angiogenesis in an in vivo Matrigel plug assay (30). Furthermore, VEGF increases expression of ATX (18,34); ATX was identified as one of the genes that control the angiogenic response to basic fibroblast growth factor (bFGF) (36). Finally, ATX-deficient mice die during embryogenesis and display a vascular defect (41,48).…”
mentioning
confidence: 99%